Knocking out histone methyltransferase PRMT1 leads to stalled tadpole development and lethality in Xenopus tropicalis - Shibata, Yuki (Biochim Biophys Acta Gen Subj, 2019)
BACKGROUND: Asymmetric arginine dimethylation of histone H4R3 to H4R3me2a by protein arginine methyltransferase 1 (PRMT1) has been implicated to play a key role in gene activation throughout vertebrates. PRMT1 knockout in mouse leads to embryonic lethality. This and the uterus-enclosed nature of the mouse embryo make it difficult to determine the development role of PRMT1 in mammals. METHODS: We took advantage of the external development of the diploid anuran Xenopus tropicalis and adapted the TALEN genome editing technology to knock out PRMT1 in order to investigate how PRMT1 participates in vertebrate development. RESULTS: We observed that PRMT1 knockout had no apparent effect on embryogenesis because normally feeding tadpoles were formed, despite the reduced asymmetric H4R3 di-methylation (H4R3me2a) due to the knockout. However, PRMT1 knockout tadpoles had severely reduced growth even with normal growth hormone gene expression. These tadpoles were also stalled in development shortly after feeding began at stages 44/45 and died within 2 weeks, well before the onset of metamorphosis. In situ analyses revealed broad cessation or drastic reduction in cell proliferation in diverse organs including the eye, brain, spinal cord, liver, and intestine. CONCLUSIONS: Our findings suggest that PRMT1 is not required for embryogenesis but is a key regulator for normal progression of vertebrate development and growth. GENERAL SIGNIFICANCE: The similarities and differences between PRMT1 knockout Xenopus tropicalis and mouse suggest that two distinct phases of vertebrate development: early embryogenesis and subsequent growth/organ maturation, have different but evolutionally conserved requirement for epigenetic modifications.